Income Inequality and Fertility Decline in China - Wang, Weijia (Journal of Modern Social Sciences, 2026)
This study examines the influence of income inequality on the declining fertility rate in China from the perspective of educational expenditure. We employ provincial panel data from the China Statistical Yearbook spanning 2011 to 2020 for empirical analysis. The findings indicate: (1) Income inequality exerts a significant negative effect on the fertility rate. (2) The income distribution gap significantly diminishes education expenditures; however, after introducing the interaction term, the impact on the fertility rate becomes significantly positive, suggesting that increased income inequality enhances the positive influence of education expenditure on the fertility rate. (3) Considering the threshold effect of income disparity, when the income gap is relatively small, it positively influences the fertility rate, as evidenced by the positive interaction term. (4) This study selects after-school tutoring expenditure as an instrumental variable because it is correlated with income and its educational resources are exogenous, satisfying the conditions for two-stage least squares regression. Tutoring affects the income gap but does not directly influence the fertility rate, ensuring the validity of our results. Finally, we evaluate the effectiveness of the two-child policy implemented in 2016 and conclude that its impact has been limited. Therefore, we recommend that the Chinese government focus on reducing the financial burden of education on families to potentially improve the fertility rate.